Rain fade analysis on earth–to-satellite microwave link operating in Comoros - Thabit, Andhraou; Abdul Malik, Noreha; Islam, Md Rafiqul; Daoud, Jamal Ibrahim (Institute of Physics Publishing, 2020)
Microwave link operates at high frequency approximately 10 GHz and above, and it suffers from high attenuation in the tropical region due to high rain intensity. Therefore, a microwave designer should consider this effect in the design so that the link can be operated with good quality of service, high availability and reliability. This study is about analysis of rain fade in a tropical country, Comoros, where the rain intensity was considered from ITU-R Recommendation. This rain intensity was used to determine the rain fade for earth-to-satellite of links operating in this country at L, C, Ka, Ku and V bands in horizontal, vertical and circular for 0.001% to 1% of exceeded per year. From the analysis, it was found that the link has availability to work from 99.999% to 99% with least effects in all frequency bands at vertical polarization, except in V-band. At 99% of availability, it shows that B-PSK is the best technique for modulation to make the proposed link more reliable. To attain 10dB fade margin which allows the antenna to reach certain quality of services, the gain receiver, diameter and figure of merit were increased while the footprint was maximized.The outcome of this study will be useful resources used to upgrade the availability and reliability of earth to satellite microwave link in Comoros.